2017
DOI: 10.5037/jomr.2017.8201
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein Coating on Titanium Implant Surface: a Systematic Review

Abstract: ObjectivesThe purpose of the study is to systematically review the osseointegration process improvement by bone morphogenetic protein coating on titanium implant surface.Material and MethodsAn electronic literature search was conducted through the MEDLINE (PubMed) and EMBASE databases. The search was restricted for articles published during the last 10 years from October 2006 to September 2016 and articles were limited to English language.ResultsA total of 41 articles were reviewed, and 8 of the most relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 40 publications
0
18
0
1
Order By: Relevance
“…In recent years, different types of coating have been introduced for clinical use: natural, peptide, ceramic, and synthetic coatings (Civantos et al, 2017). Most have been designed with osteointegration (Civantos et al, 2017;Haimov et al, 2017) and antibacterial purposes (Zhao et al, 2009;Swartjes et al, 2015;Kulkarni Aranya et al, 2017). To date, antibacterial, biodegradable perioperative coatings are designed to be loaded with gentamicin or vancomycin (Romanò et al, 2015) and are already on the market.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, different types of coating have been introduced for clinical use: natural, peptide, ceramic, and synthetic coatings (Civantos et al, 2017). Most have been designed with osteointegration (Civantos et al, 2017;Haimov et al, 2017) and antibacterial purposes (Zhao et al, 2009;Swartjes et al, 2015;Kulkarni Aranya et al, 2017). To date, antibacterial, biodegradable perioperative coatings are designed to be loaded with gentamicin or vancomycin (Romanò et al, 2015) and are already on the market.…”
Section: Discussionmentioning
confidence: 99%
“…Protein adsorption is known to be affected by various surface properties, such as roughness, organic impurities, chemical composition, van der Waals interactions, and hydrogen bonding [ 29 , 30 ]. Although many reports have described protein coating treatments of implant surfaces in the last decade, most titanium surface treatments require a period of several hours to several days [ 31 , 32 , 33 ]. However, in the present study, we performed UV pre-treatment and BMP-2 treatment for 1 min or UV pre-treatment and FN treatment for 1 h on the titanium surface for a short period of time using a simple method.…”
Section: Discussionmentioning
confidence: 99%
“…Our research team has also demonstrated that the aminogroups can be uniformly deposited on a Ti surface to bind with albumin using the promising lowtemperature plasma polymerization with allylamine approach [34]. It was found that the presence of reactive functional groups on the Ti surface significantly affects the reaction between the cell and bone tissue [35,36]. The formation of this feature can be attributed to the rapid absorption of biomolecules, mainly after the Ti implant surface is exposed to blood.…”
Section: Biocompatibility Evaluationmentioning
confidence: 94%